PENGARUH MOTIVASI KERJA TERHADAP DISIPLIN KERJA PEGAWAI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU PEKANBARU - Silvia Rahmi; Sumarno Sumarno; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of work motivation on work discipline in FKIP Riau University employees. The population used in this study were all employees of FKIP University of Riau, amounting to 49 employees. Data collection techniques by distributing questionnaires using a Likert scale. The population used in this study were all employees of FKIP University of Riau. Includes academic, general and equipment sub-sections, personnel and finance, and student affairs sub-section totaling 49 employees. The sample of this study was taken by total sampling, namely all employees of the Faculty of Teacher Training and Education, University of Riau. The data collected was then tabulated and analyzed using a simple linear regression analysis method. The results of this study indicate that the condition of work motivation of employees of FKIP Riau University Pekanbaru is good based on the results of the categorization of work motivation variables in the high category, namely 51% and the condition of work discipline of employees of FKIP Riau University Pekanbaru is quite good based on the results of the categorization of work discipline variables in the medium is 75.5%. Work motivation has a positive and significant effect on the work discipline of FKIP employees, Riau University, Pekanbaru. t count for work motivation variable is 4.859 and t table is 2,013, thus t count > t table. That is, work motivation has a significant effect on work discipline. The regression coefficient value is 0.649. The regression coefficient value is positive (+), so it can be said that work motivation (X) has a positive effect on work discipline (Y).Key Words: Work Motivation, Work Discipline